Answer:
Brainliest
Step-by-step explanation:
1 peanut before giving half
1 +1 = 2
2 before giving 2/3
2 x 3/2 = 6/2 = <em><u>3</u></em>
Answer: -9 = a(1 - 3)² + 3
Step-by-step explanation:
Vertex Form Equation:
y = a(x - h)² + k
vertex: (h, k) which means
h = 3
k = 3
because your vertex is (3, 3).
Your point is (1, -9) which is (x, y).
This means
x = 1
y = -9
Now, plug everything into your Vertex Form Equation:
-9 = a(1 - 3)² + 3
That’s your equation and final answer, but of course, if you need to, you can solve for a if you need to.
If a is positive, the parabola opens up. If a is negative, the parabola opens down.
Hope this helps!
Yes, it is a doubles fact because it has idk...